(untitled) (Research, Society and Development, 2022)
Kombucha is a fermented beverage based on black, green or oolong tea, and for the fermentation process to take place, the presence of a symbiotic culture of bacteria and yeasts, known as SCOBY, is necessary. Several studies point out the numerous health benefits associated with the consumption of this drink. Added to this, Brazil is considered one of the largest fruit producers in the world, however, around 30 to 40% of all production corresponds to co-products, most of which are incorrectly discarded. In the current context, the general objective of the work was to carry out a literature review on the applicability of fruit co-products in the development of fermented beverages of the kombucha type, characterizing it as an integrative literature review study where the selection of studies was used the PRISMA method, for data collection, the year of publication, title, objectives and journals were used, referring to the use of fruit co-products in the development of fermented beverages of the kombucha type. As a result, several studies were observed that developed kombucha-type drinks using different materials, such as: milk, coffee, cactus juice, pear, grape juice, black and red goji berries, acerola co-product and fruit pulp such as passion fruit, grape, strawberry and apple. Therefore, it is concluded that the adopted studies are innovative, being excellent guides for the beverage industry, as well as consumers who will benefit from their impact on human health, with the high nutritional value that they obtained being notorious.